Branching Pattern and Leaf Crown Architecture of Some Tree and Shrubs in Northeast Mexico - Maiti, Ratikanta; Rodriguez, Humberto G.; Sarkar, N. C.; Thakur, Ashok K. (International Journal of Bio-resource and Stress Management, 2023)
Branching pattern and crown architecture are the important component of plant growth and development of any plant species. The leaf area and photosynthesis efficiency mainly depended on the crown architecture. There are many models developed for estimation of yield of various plant products of different species in different environments. These models are used for virtual evaluation of a plant or tree species which would otherwise take decades together to know the potential of species or cultivars. Here, the research findings in this respect pertaining to the shrubs and tree species of the North East Mexico has been reviewed. The branching habit has been classified as monopodial, simpodial and pseudomonopodial, while the crown architecture as globose and irregular.